Risk of lung cancer associated with COPD phenotype based on quantitative image analysis - Schwartz, Ann G. (Cancer Epidemiol Biomarkers Prev, 2016)
BACKGROUND: Chronic obstructive pulmonary disease (COPD) is a risk factor for lung cancer. This study evaluates alternative measures of COPD based on spirometry and quantitative image analysis to better define a phenotype that predicts lung cancer risk. METHODS: Three-hundred-forty-one lung cancer cases and 752 volunteer controls age 21–89 years participated in a structured interview, standardized CT scan and spirometry. Logistic regression, adjusted for age, race, gender, pack-years, and inspiratory and expiratory total lung volume, was used to estimate the odds of lung cancer associated with FEV(1)/FVC, percent voxels less than -950 Hounsfield Units on the inspiratory scan (HU(I)) and percent voxels less than -856 HU on expiratory scan (HU(E)). RESULTS: The odds of lung cancer were increased 1.4- to 3.1-fold among those with COPD compared to those without, regardless of assessment method, however, in multivariable modeling, only percent voxels < -856 HU(E) as a continuous measure of air trapping (OR=1.04; 95% CI (1.03, 1.06)) and FEV(1)/FVC < 0.70 (OR=1.71; 95% CI (1.21, 2.41)) were independent predictors of lung cancer risk. Nearly 10% of lung cancer cases were negative on all objective measures of COPD. CONCLUSION: Measures of air trapping using quantitative imaging, in addition to FEV(1)/FVC, can identify individuals at high risk of lung cancer and should be considered as supplemental measures at the time of screening for lung cancer. IMPACT: Quantitative measures of air trapping based on imaging provide additional information for the identification of high risk groups who might benefit the most from lung cancer screening.